2000
DOI: 10.1007/s002470050748
|View full text |Cite
|
Sign up to set email alerts
|

Needle localization of small pediatric tumors for surgical biopsy

Abstract: Needle localization allows effective and less invasive excision or biopsy of a variety of small pediatric soft-tissue lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…In recent reports concerning thoracoscopic biopsies and especially removal of malignant mediastinal disease, authors reported on feasibility but were concerned about the benefit of complete resection and about potential trocar metastasis [28][29][30][31][32][33]. Under the assumption of a benign lesion, we performed a thoracoscopic complete removal of the tumor, with no problems and retrospectively without any disadvantage for our patient.…”
Section: Concomitant Lymphomamentioning
confidence: 85%
“…In recent reports concerning thoracoscopic biopsies and especially removal of malignant mediastinal disease, authors reported on feasibility but were concerned about the benefit of complete resection and about potential trocar metastasis [28][29][30][31][32][33]. Under the assumption of a benign lesion, we performed a thoracoscopic complete removal of the tumor, with no problems and retrospectively without any disadvantage for our patient.…”
Section: Concomitant Lymphomamentioning
confidence: 85%
“…7,25,47 Approaches for localization include hook wire, methylene blue injection, and/or the utilization of endoscopic ultrasound. Preoperative, image-guided, lung nodule localization, [48][49][50][51][52][53] and intraoperative ultrasound localization have been explored for lesions, especially when small and solitary. 54 A combination of computed tomography (CT)-guided microcoil localization and thoracoscopy 49 or CT-guided hook wire localization, methylene blue staining, and thoracoscopy was able to achieve a 97%-100% diagnostic yield for small subpleural lesions.…”
Section: Localization and Biopsymentioning
confidence: 99%
“…48,49,51,52 CT-guided needle localization and thoracoscopy for 0.1-cm 3 lesions were 100% diagnostic. 53 CT-guided needle localization with methylene blue staining and thoracoscopy was performed on small pulmonary nodules < 1 cm or nodules up to 2 cm deep to the pleural surface with 92.3%-100% diagnostic yield. 50,52 Minimally invasive thoracoscopic ultrasound has also been used to assist in localization of lesions between 0.3 and 2.9 cm.…”
Section: Localization and Biopsymentioning
confidence: 99%
“…Bei der transläsionalen Drahteinlegung muss bedacht werden, dass es hierbei zu einer Verschleppung von Tumorzellen kommen kann. Pulmonale Drahtmarkierungen sind bei Kindern bisher nur kasuistisch beschrieben worden [35,36] (l " Abb. 5).…”
Section: Drahtmarkierungunclassified